Lessons Learned Using a High-Definition 3-Dimensional Exoscope for Spinal Surgery. Issue 5 (14th August 2018) - Kwan, Kevin; Schneider, Julia R; Du, Victor; Falting, Lukas; Boockvar, John A; Oren, Jonathan; Levine, Mitchell; Langer, David J
Abstract: BACKGROUND: The operative microscope has significantly advanced modern neurosurgical spine surgery but continues to be limited by high costs, suboptimal optics, poor ergonomics, and difficulties with maneuverability. We believe the novel 4K high-definition (4K-HD) 3-dimensional (3D) exoscope (EX), may improve the surgical corridor through advancements in illumination, ergonomics, magnification, and depth of field and has the potential to be utilized in neurosurgical education and training. OBJECTIVE: To evaluate the surgical potential of a novel 3D EX system in spinal surgery. METHODS: Retrospective analysis over 6 mo of all patients who have undergone spinal surgery at Northwell Health using the 3D EX. Nuances of surgical theater positioning, advantages/disadvantages of the EX and clinical sequelae of the patients were analyzed. RESULTS: All 10 patients who underwent spinal surgery utilizing the EX experienced excellent surgical and clinical outcomes without complications. The low-profile EX allowed for excellent operative corridors and instrument maneuverability. The large monitor also resulted in an immersive surgical experience, and gave team members the same 3D vision as the operator. CONCLUSION: This study demonstrates the feasibility of utilizing the 3D 4K-HD EX system and highlights potential technical assets of this novel technology in regard to optics, ergonomics, and maneuverability. Further clinical research is needed to examine the clinical effectiveness of the EX system for different surgical approaches through quantitative methodology.